Gambaran Karakteristik Orang Dengan Hiv (ODHIV) Di Puskesmas Seberang Padang Tahun 2023 - Elvina Dirga Putri; Sunesni; Sri Suciana (Sekolah Tinggi Ilmu Kesehatan YPAK Padang, 2023)
HIV (Human Immunodeficiency Virus) is a virus that attacks the human immune system, so that people infected with this virus cannot prevent various types of diseases that attack their bodies. In Indonesia, in 2020 the number of HIV cases reached 543,1000 cases. This study aims to describe the characteristics of PLHIV patients at the Seberang Padang Health Center. The research was conducted at the Seberang Padang Health Center from February to August 2023 and data collection was carried out on June 25-30 2023. This type of research was descriptive with a cross-sectional method. In this study, the sample consisted of 77 respondents who were registered with PLHIV and received treatment at the puskesmas. Data processing through editing, coding, entry, tabulating, cleaning, using a univariate frequency distribution. The results showed that the most dominant description of t he characteristics of PLHIV based on age was 26-45 years old (51.9%), the highest risk factor according to sex was male 66 people (85.7%), with the most education being High school 33 people (42.9%), the most employment status is working 53 people (31.2%), with unmarried marital status as many as 58 people (75.3%).The conclusion of this research is that most of the characteristics of PLHIV are viewed from the most age, namely 26-45 years, the most gender, namely male, the most education, namely high school, the most employment status, namely working, and the most marital status, namely not married. It is recommended that people know more about the characteristics of PLHIV and prevent the causes of infection to avoid infection with PLHIV.